The Characteristics of Ahmad Shawky’s “Damascus Tragedy” Poems - Nawawi Nawawi (Insaniyat : Journal of Islam and Humanities, 2017)
Abstract Poetry is the artistic tradition that the arabs have been developing from their pre-Islamic time to the Islamic one throughout their Arabian archipelago. Next, this Arabic poetry has its own social function  as  a  note  list  (dȉwân)  for  the  Arab  people.  This  social  function  produces  the  prominent Arabic literati’s names, one of which is Ahmad Syauqi Bek bin Ali bin Ahmad Syauqi (b. in Cairo in 1868- d. in Cairo in 1932), a man of letters called the “Prince of the Poets” (amȉr al syu’arâ’). One of his well-known Arabic poetries is “Damascus Tragedy” (Nakbah Dimasyqâ) collected in the book of “A’lâm wa Ruwwâd fȉ al-Adab al-‘Arabȉ” (The Learned People and the Pioneers in the Arabic Letters) authored by Kazhim Chathiyth (1930-2007). By using an analytical descriptive method, this article aims to understand and address the literary elements of Syauqi’s thought (fikrah), his emotion (‘athȉfah), his imagination (khayâl), and his musical poems. This article suggests that Syauqi’s poems channels his various overflowing feelings, such as sadness, admiration, love, anger, and nationalism, by using the metaphorical words easy to understand the forms of the “wâfir” (literally, exuberant) and that of the rhythmical Arabic letter of “qâf”, a letter that has a strong ‘character’ in Syauqi’s poems.DOI: 10.15408/insaniyat.v1i2.5499